Pemberdayaan Guru SMP Pelita Bangsa Pamulang Penggunaan dan Pengelolaan Learning Management System - Siswanto; Gunawan Pria Utama; Wahyu Pramusinto; M. Anif; Ari Saputro; Yuliazmi; Basuki Hari Prasetyo (Ikatan Ahli Informatika Indonesia, 2021)
The Pelita Bangsa Education Foundation carries out activities in the religious, social and humanitarian fields. In the social sector established formal and non-formal educational institutions from early childhood education to higher education, including Junior High School. So far the problems with PKM partners are: Pelita Bangsa Pamulang Junior High School teachers do not have trainers to provide Learning Management System knowledge (LMS), and does not have LMS facilities to manage and upload e-learning teaching modules, and does not have the knowledge of LMS in managing and uploading fun teaching modules. The purpose of this training is to empower the Junior High School teachers to use and manage the LMS, so that teachers can deliver teaching modules that are fun, interesting, more interactive and not boring for students who are educated. With multimedia devices, manage and upload e-learning teaching modules with computers based on the LMS. The culmination of this community service activity is the development of the LMS in the form of information technology resource persons and computer training instructors for the preparation of LMS content, and the LMS training which has been carried out from January 8, 2021 to June 19, 2021, which was conducted offline taking into account the security and health conditions due to the Covid-19 pandemic. In the UAT test, a questionnaire with a Likert scale scale of 5. was used. As a result, the respondents agreed (above 86.1%) that the overall teacher empowerment training to use and management of the LMS is interesting and understanding.